An Analysis of Challenges Across the Kinnow Value Chain in Punjab: Evidence from Value Chain Actors - Jairath, Nandani; Virk, Sukhmani (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during December, 2023 to November, 2024 in the districts of Fazilka, Muktsar Sahib, and Hoshiarpur of Punjab to examine the marketing constraints encountered by key actors in the Kinnow value chain. Kinnow, a hybrid citrus fruit developed by crossing King and Willow Leaf mandarins, was introduced in Punjab during the mid-twentieth century and had emerged as one of the state’s leading commercial fruit crops. Its wide adaptability, high yield potential, and strong domestic and export demand had made it a significant contributor to farm income, rural employment, and export earnings in the state. Despite its economic importance, the Kinnow sector had continued to face persistent marketing, infrastructural, and institutional constraints that adversely affected the efficiency, competitiveness, and sustainability of the value chain. The study was based on primary data collected from 80 intermediaries, including pre-harvest contractors, wholesalers, local traders, and retailers. The respondents were selected through random sampling from the selected districts of Punjab to ensure adequate representation of marketing intermediaries. The findings revealed that high post-harvest losses, orchard theft, unregulated market competition, inadequate grading and packaging facilities, and insufficient cold storage infrastructure were the most critical constraints affecting Kinnow marketing operations. These constraints had increased transaction risks, reduced marketing efficiency, and eroded profit margins of both farmers and intermediaries, thereby weakening the overall performance and resilience of the Kinnow value chain. The study emphasized targeted policy interventions, investment in post-harvest management and cold chains, and stronger coordination among value chain actors for sustainability in Punjab.